Design and Build an Arduino Mega-Based Automatic Lawn Mower - M. Septian Septian (Cattleya Darmaya Fortuna, 2022)
Technology is a new breakthrough to create products in the form of goods or services that can make human work easier. With the growing use of technology to facilitate human work, humans continue to innovate in creating new technologies in order to maximize the resources they have and relieve human labor. All slowly can be found and felt in everyday life. Ranging from smart homes (Smart Home), smart cars (Smart Car), smart watches (Smartwatch), electronic learning, to smart machines that can work by themselves and much more. The purpose of this final project is the creation of a lawn mower automatically and connected to a smartphone. The final project method is data collection, design stages, testing tools and systems. The result of the final project is the existence of an automatic lawn mower that is connected to a smartphone designed using a mega 2560 microcontroller